Efektivitas Kinerja Pegawai Dalam Meningkatkan Pelayanan Publik di Kantor Camat Lemito Kabupaten Pohuwato - Naldiyanto Mukusibu; Yanti Aneta; Yacob Noho Nani (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the effectiveness of employee performance in improving public services at the Lemito Sub-District Office, Pohuwato Regency, Gorontalo Province. This study is motivated by the presence of slow services, service times that do not comply with the Standard Operating Procedure (SOP), and the low discipline of employees in performing their duties. This study employs a descriptive, qualitative method, utilizing interviews, observations, and documentation. The study focuses on three main aspects, namely quantity of work, quality of work, and time utilization. The findings show that the quantity of employee performance is considered adequate, as reflected in the services successfully completed. However, the quality of work is still not optimal, as various errors, including clerical errors and a lack of accuracy, are still found in the work. Time utilization is also not yet optimal, as evidenced by services that exceed the Standard Operating Procedure (SOP) and some employees who have not been able to fully utilize their working hours in carrying out their duties. Thus, this study recommends improving work discipline, implementing SOPs consistently, and providing training to improve employee skills.